Taxonomic revision of Leucascus Dendy, 1892 (Porifera: Calcarea) with revalidation of Ascoleucetta Dendy & Frederick, 1924 and description of three new species - Cavalcanti, Fernanda F.; Rapp, Hans Tore; Klautau, Michelle (Zootaxa, 2013)
Sponges of the genus Leucascus are frequently recognised as possessing anastomosed tubes with choanocytes, and cortical and atrial membranes with pinacocytes. In the last years, five species of other genera were transferred to Leucascus, and several other species were suggested but not formally included in this genus. In the present work, all these species accepted or suggested as Leucascus were revised. According to our results, Leucascus is now composed of nine species: L. clavatus, L. leptoraphis comb. nov., L. lobatus, L. neocaledonicus, L. protogenes comb. nov., L. roseus, L. simplex (type species), L. albus sp. nov., and L. flavus sp. nov. The presence of spines in the apical actine of the tetractines had never been observed in Leucascus, but it was found in all species with tetractines in their skeletons. Some species were transferred from Leucascus to the genus Ascoleucetta, which is revalidated here based on important differences in the cortex. Modifications are also proposed in the definition of both genera. Based on our results, the family Leucascidae is now composed of Ascaltis, Leucascus and Ascoleucetta.